“WHAT FATWOOD DECAYS, WHAT WORD DECAYS”: TOWARDS A TANGKHUL PAREMIOLOGICAL MINIMUM - Ng, Mawonthing (Proverbium - Yearbook, 2025)
This paper examines the data drawn from a survey conducted in 2020 among Tangkhul diasporic students in Shillong, Meghalaya, regarding their familiarity with and use of some traditional proverbs and proverbial phrases. This is in response to the growing concern in the community regarding the cultural competence of the younger generation. Given their status as repositories of ancestral wisdom, proverbial usage in contemporary communication must have very specific modes of operation. The aim of this study is, therefore, twofold: firstly, to gauge the proverbial literacy of younger Tangkhul diasporic speakers and to try to understand the contemporary currency of Tangkhul fixed expressions among a globalised youth. The proverbial literacy of 129 college-educated urban Tangkhul youth aged between 19 and 33 years was tested using snowball sampling to determine the contemporary relevance of these proverbs among the young diaspora. While the small sample size inhibits the establishment of a paremiological minimum, the findings are useful for the understanding of cultural continuities and shifts among the Tangkhul Naga, especially given the UNESCO status of the language as endangered. The findings show that although over 50 percent of speakers have low proverbial literacy, a significant number do possess active knowledge. These insights contribute not only towards establishing a paremiological minimum for Tangkhul, but also potentially address questions of cultural influence, diasporic identities, and the ability of fixed expressions to survive even in the absence of current cultural referents.